Håp og livsmot i sykdomsfortellinger etter hjerneslag - Kitzmüller, Gabriele (Nordisk tidsskrift for helseforskning, 2019)
Hope and life courage in illness narratives after stroke This essay illuminates the meaning of hope and life courage in the narratives of Tomas and Maria, a couple who had experienced the life changing consequences of Maria’s stroke. Hope is supported by the couple’s strong and loving relationship and by empathy and caring in their relationships with professional caregivers. In this way, the relational component of hope is revealed as the most important prerequisite for maintaining hope. The analysis demonstrates that life courage and hope are strongly needed for trust in the future and rehabilitation efforts. However, careless and unprofessional attitudes and practices of clinicians may lead to loss of control, poorer self-image and hopelessness. To support the hope of patients and relatives, clinicians must show caring attitudes and use both medical and humanistic knowledge. They should not devalue the phenomenon of hope as unrealistic.